EVALUATION OF THE BIOLOGICAL EFFECT SYNTHESIZED ZINC OXIDE NANOPARTICLES ON PSEUDOMONAS AERUGINOSA - Alaa Alden, M. A.; Yaaqoob, L. A. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to demonstrate the biosynthesis procedure of Zinc oxide nanoparticles (ZnO NPs) using Prodigiosin pigment which in turn produced from particular environmental bacteria isolates Serratiamarcescensas a stabilizing and reducing agent. Additionally, the synthesis conditions were precisely taken into consideration as a pH of 7 and a temperature of 50°C alongside a concentration of prodigiosin of 12 mg/ml with 5mg precursor of zinc acetate in deionized distilled water (DDW) 50ml. Biosynthesized ZnO nanoparticles have presented many applications such as catalysis, biosensing, anticancer, and biomedical, etc. The optimum condition for ZnO biosynthesis was characterized through several techniques such as UV-Vis, AFM, XRD, FT-IR, and FE-SEM. In particular, a cut-off phenomenon of the biological synthesized ZnO was found at around 280 nmusing UV-Vis, while spherical shape particles were noticed using FE-SEM techniques. Also, the AFM analysis revealed that ZnO NPs an average diameter size of 45.02 nm.And the effect of ZnO NPs on bacteriaPseudomonas aeruginosaon an inhibition zone 29mm.